Ulumul Hadis Sebagai Pondasi Pemikiran Moderat Mahasiswa FEBI IAIN Pontianak - Abdurrahman Abdurrahman; Mujahidatul Khaerat (El Nubuwwah Jurnal Studi Hadis, 2023)
This article reveals the existence of the course "Ulumul Hadis" that serves as the foundation for a Moderate Understanding among students of the Faculty of Islamic Economics and Business (FEBI) at the State Islamic Institute (IAIN) in Pontianak, which is located in West Kalimantan Province, a province known for its diversity in terms of ethnicity, customs, and religion, so there is potential for disputes and conflicts. This article is a library research that uncovers the moderate values from the Ulumul Hadis material as well as its teaching methods. Therefore, the method used is qualitative research with a descriptive approach, subsequently gathering data through literature studies or documents that have discussed this theme, while directly observing the environment at FEBI IAIN Pontianak, so that the collected data can be verified and revealed with good results. The instilling of moderate values in the students of FEBI IAIN Pontianak is largely derived from the Ulumul Hadis material taught by a lecturer. Among the materials are hadiÌ„s á¸aif, hadiÌ„s Mauá¸uÌ„â€™, AsbaÌ„b al-WuruÌ„d and textual and contextual understanding of hadith.